Cyclodextrin based polymer sorbents for micro-solid phase extraction followed by liquid chromatography tandem mass spectrometry in determination of endogenous steroids - Manaf, N.A. (Elsevier B.V., 2018)
Sorbents were prepared by cross-linking Î²-cyclodextrin (Î²-CD) using two different types of cross-linker units at variable reactant mole ratios. The resulting polymers containing Î²-CD were evaluated as sorbents in micro-solid phase extraction (Î¼-SPE) format for the extraction of the endogenous steroids testosterone (T), epitestosterone (E), androsterone (A), etiocholanolone (Etio), 5Î±-androstane-3Î±,17Î²-diol (5Î±Adiol) and 5Î²-androstane-3Î±,17Î²-diol (5Î²Adiol). The best sorbent (C1; cyclodextrin polymer) showed superior extraction characteristics compared with commercial sorbents (C18 and Bond Elut Plexa). Parameters influencing the extraction efficiency of the C1 sorbent such as extraction and desorption times, desorption solvent and volume of sample were investigated. The extracts were separated using a Hypersil Gold column (50 Ã 2.1 mm, 1.9 Î¼m) under gradient elution coupled to a LCâMS/MS. The compounds were successfully separated within 8 min. The method offers good repeatability (RSD < 10) and linearity (r2 > 0.995) were within the range of 1â200 ng mLâ1 for T and E, 250â4000 ng mLâ1 for A and Etio and 25â500 ng mLâ1 for 5Î±Adiol and 5Î²Adiol, respectively. The method was applied for the determination of steroid profile of urine from volunteers. Â© 2018 Elsevier B.V.